PELATIHAN PENDAMPINGAN MEMBACA CERITA BERSAMA ORANG TUA DALAM MENUMBUHKAN MINAT BACA ANAK [TRAINING ASSISTANCE READING STORIES WITH PARENTS IN GROWING CHILDREN'S READING INTEREST] - Yubali Ani; Chandra Han; Kusuma Wardhani; Ganda Sari (Jurnal Sinergitas PKM & CSR, 2021)
In order to foster the capability of literacy in the community, Kindergarten Al-Amin, Ciputat has received books from Rebung Cendani Foundation These books have not been used maximally to increase students' literacy. Therefore, this Community Service will provide training and assistance to parents of the students on how to read story books to their children at home. Assistance was provided by Al-Amin teachers with the direction of community services facilitators for three months. Parents and teachers will practice the reading in accordance with the steps that have been explained. The mentoring training activities went smoothly. Through this mentoring training parents become anthusiastic in implementing reading activities at home with their children, reading activities also help parents keep children away from gadgets, and parents gain knowledge about reading fun stories. Suggestions from this mentoring training activity can foster a reading habit among Kindergarten Al-Amin. BAHASA INDONESIA ABSTRACT: Dalam rangka program menumbuhkan minat baca di masyarakat, TK Al-Amin, Ciputat mendapatkan bantuan buku-buku dari Yayasan Rebung Cendani. Buku-buku tersebut belum dimanfaatkan secara maksimal untuk meningkatkan literasi para murid. Oleh karena itu, kegiatan PkM ini memberikan pelatihan dan pendampingan kepada orang tua murid mengenai bagaimana membaca buku cerita kepada anak-anaknya di rumah. Pendampingan diberikan oleh guru-guru TK Al-Amin dengan arahan fasilitator PkM selama tiga bulan. Dalam proses pendampingan orang tua dan guru melakukan latihan membaca sesuai dengan langkah-langkah yang sudah dijelaskan. Kegiatan pelatihan pendampingan berjalan dengan baik. Melalui pelatihan pendampingan ini orang tua menjadi antusias didalam menerapkan kegiatan membaca di rumah dengan anak masing-masing, kegiatan membaca juga membantu orang tua menjauhkan anak dari gadget, dan orang tua memperoleh pengetahuan mengenai membaca cerita yang menyenangkan. Saran dari kegiatan pelatihan pendampingan ini dapat menumbuhkan kebiasaan membaca dikalangan TK Al-Amin.